Between empowerment and abuse: citizen participation beyond the post-democratic turn. Issue 3 (2nd April 2020) - Butzlaff, Felix
ABSTRACT: In this special issue on "Democratization beyond the Post-Democratic Turn. Political Participation between Empowerment and Abuse", we have explored changing understandings of participation in contemporary Western representative democracies through the analytical lens of the concept of the post-democratic-turn. We have investigated technology-based, market-based, and expert-led innovations that claim to enhance democratic participation and to provide policy legitimation. In this concluding article, I revisit the cases made by the individual contributors and analyse how shifting notions of participation alter dominant understandings of democracy. I carve out how new and emerging ideas of participation are based on different understandings of political subjectivity; furthermore, how constantly rising democratic expectations and simultaneously increasing scepticism with regard to democratic processes and institutions point to a growing democratic ambivalence within Western societies. Making use of Dahl's conceptualization of democracy, in this article, I review changing understandings of participation in light of their contribution to further democratization. The article shows how under post-democratic conditions the simulative performance of autonomy and subjectivity has become central to democratic participation. It emphasizes that what in established perspectives on democratization might appear as an abuse of participation, through the lens of a post-democratic-turn might be perceived as emancipatory and liberating.